Evaluation of complications, conversion rate, malignancy rate, and, surgeon's experience in laparoscopic assisted supracervical hysterectomy (LASH) of 1274 large uteri: A retrospective study - Garri Tchartchian; Bernd Bojahr; Harald Krentel; Rudy L. De Wilde (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Hysterectomy now belongs to standard gynecological procedures. Moreover, a shift towards laparoscopic techniques is ever more apparent as they provide many advantages such as less traumatization and shorter convalescence. Large uteri are still mentioned as contraindications for laparoscopic hysterectomy even though those patients might benefit from the lower morbidity associated with minimal invasive techniques. In this study, the largest reported so far, we analyzed intraoperative and postoperative complications as well as the surgeon's experience of laparoscopic assisted supracervical hysterectomy (LASH) in patients with a uterus weight over 500 g. Material and Methods The present retrospective study, between June 27, 1998 and August 31, 2019, evaluates 1274 patients with a uterus weight over 500 g who were treated with LASH for benign uterine diseases at the Clinic for Minimal Invasive Surgery (Berlin, Germany). All surgeries were performed by one of four in‐house surgeons with experience in LASH: they had performed at least 500 LASH procedures before the study. Patients receiving surgical treatment for malignant tumors were not included in the study. Major and minor intraoperative and postoperative complications were recorded and evaluated. Additionally, medical files were evaluated for demographic data, American Society of Anesthesiologists score (I–IV), name of the surgeon, duration and indication for surgery, history of previous gynecological procedures and concomitant surgical interventions, weight of removed uterine tissue, duration of postoperative hospitalization in patients with complications, intraoperative conversion from laparoscopy to laparotomy, and malignancy rate. Results The mean age was 47.0 ± 7.3 years and mean body mass index was 25.6 ± 7.1 kg/m2. Average parity was 1.04 ± 1.57. Average uterus weight was 761.8 ± 317.9 g (500–4065 g). The mean duration of surgery was 96.9 ± 49.5 min; 54% of all patients were treated without concomitant intervention, conversion rate was 2.12%. The malignancy rate was 0.4% and the complication rate was 6.81% with 1.36% intraoperative complications and 5.45% postoperative complications. Conclusions The overall low complication and malignancy rates observed in this study allow us to present LASH as a safe and efficient alternative laparoscopic approach to remove uteri of any size in the hands of experienced surgeons.